Seasonal Employee Retention in the Hospitality Industry: A Case of Antalya - Arıcı, Hasan Evrim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
A careful investigation of the hospitality literature shows that the majority of management studies have generally focused on full-time hotel employees, but any research has not specifically focused on management of seasonal employees. Hence, there is a necessity for a new research model to retain seasonal employees in the industry by increasing of the supervisors‟ management understandings, qualities, and policies in managing their organizations effectively and efficiently. This multilevel study investigates the effects of perceived supervisor support on seasonal hotel employees‟ turnover intention by focusing on the mediator influence of work engagement and the moderator influence of authentic leadership. Data were collected from a sample of seasonal workers working at 5-star hotel facilities in Antalya. Having utilized time-lagged data from 305 seasonal employees who came from 57 work groups in twenty-five 5-star hotel organizations in Turkey, Hierarchical Regression Analysis, Hayes‟ Mediation Analysis, and Hierarchical Linear Modelling were conducted to investigate the hypothesized relationships. In line with the social exchange theory, the results demonstrate that supervisor support is a key to boosting seasonal employees‟ work engagement. Supervisor support perceived by seasonal employees and authentic leadership also reduced intention to leave the organization. In addition, based on the social identity theory, hierarchical linear modelling displayed that authentic leadership moderates the negative influences of perceived supervisor support on employee turnover intention. Due to high turnover rate, having engaged seasonal employees who prefer the same hotel organization for the next season is a key for keeping high service quality standards and organizational success eventually. This research presents how seasonal employees can be reengaged and retained through supervisor support as well as the moderating role of authentic leadership. This study makes a considerable contribution to the academic world as to a growing challenge that has crucial influences on both organizations and society at large.

ÖZ: Günümüze kadar yapılan çalışmaların büyük çoğunluğu turizm ve otelcilik sektöründe kadrolu çalışanların yönetimi üzerine yoğunlaşmışlardır. Ancak sezonluk otel çalışanlarının nasıl yönetileceği, bu çalışanların sektörde nasıl tutulabileceği konusu maalesef mevcut alan yazında göz ardı edilmiştir. Bu nedenle, otel yöneticilerinin yönetim anlayışları, yeterlilikleri ve politikalarını geliştirerek sezonluk çalışanların işletmede tutulmasını ve devamlılığının nasıl sağlanabileceğini öneren yeni bir araştırma modeline ihtiyaç duyulmaktadır. Çalışmanın temel amacı, algılanan yönetici desteğinin sezonluk çalışanların işten ayrılma niyeti üzerine etkisini çalışanların işe bağlılığının aracı rolü ile otantik liderliğin düzenleyici (moderatör) rolü üzerine yoğunlaşarak araştırmaktır. Araştırma kapsamında veriler Antalya‟da faaliyet gösteren 5 yıldızlı otellerde görevli 57 çalışma grubunu oluşturan 305 sezonluk çalışandan toplanmıştır. Çalışmanın modeli Hiyerarşik Regresyon Analizi, Hayes‟in Aracı (Mediation) Analizi ve Hiyerarşik Lineer Model kullanılarak analiz edilmiştir. Sosyal değişim teorisi bağlamında, çalışma sonuçları göstermektedir ki, algılanan yönetici desteği sezonluk çalışanların işe bağlılığını arttıran temel faktördür. Ayrıca, algılanan yönetici desteği ve otantik liderlik sezonluk çalışanların işten ayrılma niyetini azaltmaktadır. Diğer taraftan, sosyal kimlik teorisi temelinde, hiyerarşik lineer modelleme analizi göstermektedir ki otantik liderlik, algılanan yönetici desteğinin çalışanların işten ayrılma niyeti üzerine etkisinde düzenleyici role sahiptir. Otelcilik endüstrisinde çalışanların işten ayrılma oranının oldukça yüksek olmasından dolayı, yüksek turizm sezonunda aynı otele çalışmaya gelen işine bağlı sezonluk çalışanlara sahip olmak otelin servis kalitesinin ve nihayetinde kurumsal başarısının artması için temel bir faktördür. Bu çalışma, algılanan yönetici desteği ve otantik liderliğin düzenleyici etkisi sayesinde sezonluk çalışanların işletmede tutulabileceğini göstermektedir. Çalışma bulguları akademik dünyaya her geçen yıl büyüyen ve otel işletmeleri üzerine önemli etkilere sahip olan sezonluk istihdam konusunda önemli katkılar sunmaktadır.
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Co-Supervisor: Prof. Dr. Hasan Kılıç and Supervisor: Prof. Dr. Hüseyin Araslı.
Keywords: Tourism; Tourism Employees--Supply and demand--Antalya (Turkey); Hospitality industry--Employees--Seasonal Employees--Antalya (Turkey); Hospitality management; supervisor support; work engagement; authentic leadership; seasonal employee retention; multi-level analysis; Turkey